Artistic Narratives in Advertising and Consumer Behavior: A Dual-Mediation Model based on Symbolic Interactionism (Journal of Global Arts Studies, 2025)
Background： With the growth of mobile internet and social media, 'storytelling advertising' is a key brand strategy, leading to budget increases for narrative-capable digital and video scenarios. As an artistic narrative form, it blends visual symbols, aesthetics, and creative plots to offer a unique aesthetic experience. Existing studies confirm it affects consumer decisions via emotional resonance, but the symbolic meaning construction remains underexplored. Since Zaltman (2003) noted 95% of purchase decisions are subconscious, emotion's leading role in consumer decisions is critical. Objective： From the symbolic interactionism perspective, this study explores the dual-mediation mechanism (emotional resonance, brand identification) through which advertising artistic narratives influence consumers’ purchase intention, and quantifies the two paths’ effect strength. Methods: Based on symbolic interactionism and narrative transportation theory, we developed the model "artistic narrative→emotional resonance/brand identification→purchase intention"; We surveyed 450 Chinese young consumers (18-30, purchasing power; 90% valid), using a 5-point Likert scale to measure artistic narrative features (narrativity, interactivity, emotional appeal), emotional resonance, brand identification and purchase intention. Hypotheses were tested via SEM with 5,000-sample Bootstrap. Results: Narrativity, interactivity and emotional appeal all positively influence emotional resonance; emotional appeal has the strongest impact on brand identification. Both mediators positively affect purchase intention, with emotional resonance’s mediating effect significantly stronger than brand identification’s. Conclusion: Emotional resonance is the key pathway for artistic narratives to drive purchase intention, with brand identification as a support. This study extends symbolic interactionism to advertising artistic symbol construction, guiding scenario-specific, artistically engaging ad design. Limited to Chinese youth, future research could expand to cross-cultural/elderly samples and explore effects of different artistic styles and media carriers.
Keywords: Artistic Narrative in Advertising; Emotional Resonance; Brand Identification; Purchase Intention